ANALISIS POLA ASUH ORANG TUA TERHADAP HASIL BELAJAR SISWA KELAS IV di SD N TIMBANG 01 - Herwiyanto, Annisa Putri; Kusumawati, Dian; Wuryani, Meilan Tri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of parenting styles on the learning outcomes of fourth-grade students at SD N Timbang 01. The study uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. There are three research questions in this study, namely, how parenting styles are applied in assisting learning at home, what factors influence the effectiveness of parenting styles in supporting student learning outcomes, and whether parenting styles contribute to student learning outcomes. The research informants consisted of classroom teachers, parents, and students selected using purposive sampling. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results showed that parenting styles play an important role in shaping students' motivation, discipline, and consistency in learning. Democratic parenting styles were found to produce optimal and stable learning outcomes because they are supported by clear learning rules, parental guidance, and two-way communication that encourages children's intrinsic motivation. Authoritarian and mixed parenting styles tend to produce fluctuating learning outcomes because children's learning motivation is more external and influenced by pressure, such as punishment and threats. Meanwhile, permissive parenting shows relatively low learning outcomes due to a lack of rules and supervision, resulting in children being less disciplined and distracted.